Materials science and design for engineers - Huda, Zainul; Bulpett, Robert (Materials science foundations, 2012)
The uniqueness of the title of this book, Materials Science and Design for Engineers, already indicates that the authors - professionals having over 30 years of experience in the fields of materials science and engineering - are here tackling the rarely-discussed topic of the science of materials as directly related to the domain of design in engineering applications. This comprehensive textbook has now filled that gap in the engineering literature. Review from Book News Inc.: This textbook is intended for engineering students taking their first course in materials science and engineering. The.